Variability Analysis and Forecasting of Relative Humidity in Bangladesh - Syeda, JA (Journal of Environmental Science and Natural Resources, 2013)
An attempt was made to investigate the trend and variability pattern for decadal, annual and seasonal (three crop seasons) average relative humidity (ARH) of six divisional stations in Bangladesh: Dhaka, Rajshahi, Khulna, Barisal, Sylhet and Chittagong. The rates of linear trend (LT) for minimum, maximum and range humidity were examined too. The monthly ARH for 2009-2012 were forecasted using the univariate Box-Jenkins ARIMA (autoregressive integrated moving average) modelling technique. The rates of LT for annual ARH were found negative for Dhaka and Chittagong but positive for others. The rates were found negative for all the coefficient of variations (CVs). The rate for annual minimum humidity was positive for Dhaka but negative for others. The rates for annual maximum and range humidity were negative for Dhaka and Chittagong but positive for others. The rates for seasonal ARH were negative for Dhaka while positive for Rajshahi and Barisal in all the three seasons. It was negative for Kharif season, whereas positive for Prekharif and Rabi seasons for Khulna and Sylhet. It was negative for Kharif and Prekharif seasons, as the same time as positive for Rabi season for Chittagong. DOI: http://dx.doi.org/10.3329/jesnr.v5i2.14805 J. Environ. Sci. & Natural Resources, 5(2): 137-147 2012